Fostering Translating Skills to Young Learners: A Case Study - Anggarini, Ida Fitri (Universitas Siliwangi, 2024)
This case study explores strategies for fostering translation skills in young learners at MI Miftahul Huda Ngadireso, Malang, Indonesia. It delves into the importance of language acquisition during the early stages of education and examines specific methodologies used to enhance translation abilities. The study assesses the impact of interactive and immersive approaches on linguistic development, providing insights into effective pedagogical practices for nurturing basic translational proficiency in young language learners. This study indicates that Shobahul Lughah (morning language learning) effectively improves students’ translating skills. Furthermore, the study emphasises the value of constant practice and exposure to varied language inputs in developing fluency and accuracy in translation tasks. Moreover, the study emphasises the importance of taking a balanced approach to language training that includes both explicit and implicit learning possibilities. While explicit education offers learners systematic guidance and unambiguous explanations of linguistic topics, implicit learning experiences promote inquiry, discovery, and subconscious internalisation of language patterns and conventions. Finally, by embracing novel pedagogical approaches and establishing a supportive learning community, educators may help young students become efficient interpreters and communicators in an increasingly interconnected global world. Keywords: Translating; Young Learner; and Skills.